2009
DOI: 10.1186/1471-2202-10-63
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proton magnetic resonance spectroscopy reveals region specific metabolic responses to SIV infection in the macaque brain

Abstract: Background: In vivo proton magnetic resonance spectroscopy ( 1 H-MRS) studies of HIV-infected humans have demonstrated significant metabolic abnormalities that vary by brain region, but the causes are poorly understood. Metabolic changes in the frontal cortex, basal ganglia and white matter in 18 SIV-infected macaques were investigated using MRS during the first month of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
41
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 54 publications
12
41
2
Order By: Relevance
“…Longitudinal SIV/macaque studies report an initial elevation of Cho/Cr in acute infection that is subsequently reduced during the transition from acute to primary infection. 27,28 Studies with human participants show a similar progression with elevated Cho/Cr at 16-17 days postexposure 10 followed by lower Cho, 15 consistent with our results of lower Cho/Cr and MI/Cr months after exposure. A plausible biological mechanism for the low Cho/Cr and MI/Cr in PHI may be the result of reduced viral load after the acute phase 24 and concomitant reduced membrane turnover and gliosis related to immune stabilization.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 80%
“…Longitudinal SIV/macaque studies report an initial elevation of Cho/Cr in acute infection that is subsequently reduced during the transition from acute to primary infection. 27,28 Studies with human participants show a similar progression with elevated Cho/Cr at 16-17 days postexposure 10 followed by lower Cho, 15 consistent with our results of lower Cho/Cr and MI/Cr months after exposure. A plausible biological mechanism for the low Cho/Cr and MI/Cr in PHI may be the result of reduced viral load after the acute phase 24 and concomitant reduced membrane turnover and gliosis related to immune stabilization.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 80%
“…35,[39][40][41][42] The region-dependent patterns in evolution were seen in the present study as well. Significant reduction of MTR in the centrum semiovale, splenium, and putamen was observed as early as 2 weeks after SIV infection while such alterations lagged behind in genu, thalamus, FWM, caudate, and FGM, revealing regional differences in MTR changes in the cerebral microstructural.…”
supporting
confidence: 66%
“…For example, reduced Glx concentrations have been observed in Alzheimer's disease (Antuono et al, 2001;Jones and Waldman, 2004). In HIV, human and animal models have shown decreased levels of cerebral Glx Ratai et al, 2009;Chang et al, 1997), including patients with progressive multifocal leukoencephalopathy. Another study showed decreased frontal Glx concentrations, along with increased white matter integrity on diffusion tensor imaging among patients treated with lithium for HIV-associated cognitive impairment (Schifitto et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%